RETRACTED: The Multi-Station Fusion-Based Radiation Source Localization Method Based on Spectrum Energy - Guojin He; Yulong Hao; Yaocong Xie (Sensors)
Today’s highly complex and rapidly changing electromagnetic environment places higher demands on the precise localization of illegal radiation sources. In response to this, this paper innovatively proposes a multi-station fusion-based radiation source localization method, which leverages the frequency, field strength, bandwidth, and other characteristic information embedded in frequency band scanning data. The method thoroughly explores the energy characteristics of the detected radiation sources while closely integrating the objective laws of propagation attenuation in electromagnetic space. By employing an advanced, normalized power calculation technique, it successfully achieves high-precision localization of the radiation source. Through rigorous and thorough experimental validation, this method reduces localization errors by 25% and cuts the equivalent radiation power error by 30% compared to traditional localization methods. This achievement provides more reliable and accurate technical support for applications in the electromagnetic field, offering promising prospects for advancing and refining electromagnetic environment monitoring and management technologies.